Landscape changes in the Pivka area, Slovenia - Pirnat, Janez (Zbornik gozdarstva in lesarstva, 2012)
Spontaneous afforestation is one of the biosystemic landscape change processes affecting landscape functioning. The process of overgrowing is highly dynamic, and the temporal dimension of changes in landscape structure can be of key importance for evaluating habitat suitability. A detailed study was carried out in the area of 19.52 km2 within the Pivka municipality, where land use is a mixture of traditional farmland, forests, and extended areas of abandoned former farmland with natural re-growth. In addition, this area is highly important for two bird species: the Barred Warbler (Sylvia nisoria) and the Red-backed Shrike (Lanius collurio). Both species are sensitive to forest spreading and prefer a mixture of extensive meadows with shrubs and hedgerows as their most suitable habitat. Digital BW orthophotos from the 1975 - 2000 period and colour digital orthophotos from 2009 have be enused for on screen digitizing of the EUNIS habitat classes. Indicators of landscape changes were derived from temporal based difference in the landscape structure (different structural indicators based on patch size, shape, distances and patch dynamics). All the details obtained were evaluated based on Earth observation data and GIS supported methods. The most valuable parts of the area for both species are, from a biodiversity point of view, the core forest areas and mixture of meadows with shrubs and hedgerows.
Keywords: analiza habitatov; EUNIS; kazalci; krajinska zgradba; Pivka; zaraščanje